Impact of economic uncertainty in a small open economy: the case of Chile. Issue 26 (3rd June 2018) - Cerda, Rodrigo; Silva, Álvaro; Valente, José Tomás
ABSTRACT: We construct the first news-based economic uncertainty index for Chile, which allowed us to rebuild 23 years of the history of economic uncertainty in the country and quantify its impact on the economy. We find that an increase in economic uncertainty conveys a fall in GDP, investment, and employment, even after accounting for the small open economy nature of Chile. In contrast to previous studies for big and developed economies, we do not find evidence of an overshooting effect when uncertainty dissipates; therefore, increases in economic uncertainty have negative effects on the economy, even in the long-run. Our estimates suggest that these impacts range from 10% to 20% for aggregate investment, 2.5% to 5% for GDP, and 1.3% to 4.2% for employment. Extensions suggest that economic uncertainty affects both mining and non-mining investment, with the former showing a more pronounced decline. We also find that the bulk of effect of economic uncertainty on aggregate investment is via private investment, with some short-run impacts on public investment. Moreover, compared to the GDP response, aggregate consumption responds in almost the same way to an economic uncertainty shock.